Positive electrode lithium supplementing material and preparation method thereof, positive electrode plate and lithium ion battery

Through the coordinated cooperation of titanium doping and carbonized carbonized carbon coatings derived from MOFs materials, the problems of gas production and polarization of lithium ferrate materials during the decomposition process are solved, and the charging and discharge capacity, rate performance and cycle stability of lithium-ion batteries are improved. , achieving synchronous improvement of battery performance and safety.

CN119447299APending Publication Date: 2025-02-14福建龙净储能电池有限公司 +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411513023.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Lithium ferrate material has severe gas production and polarization in the process of decomposing and producing active lithium, resulting in cell circulation attenuation, increased internal resistance, and reduced power and battery safety.

Method used

Through the coordinated coordination of titanium doping and carbonized carbon coatings derived from MOFs materials, the stability and lithium supplementation effect of lithium ferrate materials are improved. Titanium doping increases the lattice defects of the material and improves the diffusion rate of lithium ions; MOFs material derived carbonized carbon cladding increases the conductivity and porosity of the material, enhances the wettability of the electrolyte and reduces resistance.

Benefits of technology

It significantly improves the charging and discharge capacity, rate performance and cycle stability of lithium-ion batteries, improves the capacity attenuation problem after the first charge, and improves the overall performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105934600000171
    Figure BDA0005105934600000171
  • Figure BDA0005105934600000181
    Figure BDA0005105934600000181
Patent Text Reader

Abstract

The invention provides a positive electrode lithium supplementing material and a preparation method thereof, a positive electrode plate and a lithium ion battery. The positive electrode lithium supplementing material comprises an inner core and a carbon coating layer coating the surface of the inner core, the inner core comprises a titanium-doped lithium ferrite material, and carbon in the carbon coating layer is obtained by deriving and carbonizing an MOFs material. According to the positive electrode lithium supplementing material provided by the invention, through the synergistic cooperation of titanium doping and the carbon coating layer derived and carbonized by the MOFs material, the stability is good, and the lithium supplementing effect is excellent, so that the charge-discharge capacity, the rate capability and the cycling stability of a battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a positive electrode lithium supplement material and a preparation method thereof, a positive electrode plate and a lithium ion battery. Background Art

[0002] As an emerging green energy storage method, batteries have been widely studied and applied in the field of energy storage. Among them, lithium-ion batteries are one of the most representative batteries at present. During the first charging process of lithium-ion batteries, a solid electrolyte film (SEI) will be generated on the surface of the negative electrode, causing a large number of lithium ions to lose their activity and become "dead lithium", consuming the lithium ions in the positive electrode material, reducing the first cycle coulomb efficiency (ICE) of the battery, and affecting the battery performance. In order to solve the above defects and improve the energy density of lithium-ion batteries, lithium replenishment technology is usually used to compensate for the loss of active lithium in the first week of charging and discharging of the battery. Lithium replenishment technology can be divided into positive electrode lithium replenishment and negative electrode lithium replenishment. Compared with the complex and high-cost negative electrode lithium replenishment, positive electrode lithium replenishment is compatible with the existing electrode manufacturing process and is easier to apply.

[0003] Currently, lithium ferrite (Li5FeO4) has attracted people's attention due to its good compatibility with battery systems, low production cost, non-toxicity and high gram capacity (860mAh / g). Lithium ferrite (Li5FeO4) has abundant raw materials, low price, environmental friendliness, excellent thermal stability and safety, and its gram capacity is more than three times that of common positive electrode materials. Therefore, it is often used as a positive electrode material lithium supplement. However, based on the study of the stability and surface properties of lithium ferrite, it was found that the material has serious gas production and polarization in the process of decomposing and producing active lithium. This problem will eventually lead to problems such as battery cell cycle attenuation, increased internal resistance, and reduced power and battery safety.

[0004] Therefore, how to enhance the stability of lithium ferrite materials and improve the lithium replenishment effect is a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a positive electrode lithium replenishing material and a preparation method thereof, a positive electrode plate and a lithium ion battery. The positive electrode lithium replenishing material provided by the present invention has good stability and excellent lithium replenishing effect through the synergistic combination of titanium doping and carbonized carbon coating layer derived from MOFs material, thereby improving the charge and discharge capacity, rate performance and cycle stability of the battery.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a positive electrode lithium replenishing material, which includes a core and a carbon coating layer coated on the surface of the core; the core includes titanium-doped lithium ferrite material, and the carbon in the carbon coating layer is derived from MOFs material and carbonized.

[0008] In the present invention, titanium doping can increase the lattice defects of lithium ferrite materials, which is beneficial to improve Li + The diffusion rate inside the material and the conductivity of the particles effectively improve the initial charging capacity of the lithium-ion battery and improve the problem of capacity attenuation after the first charge; the synergistic combination of the carbonized carbon coating layer derived from the MOFs material, which is also doped with metal elements in the MOFs material, can prevent lithium ferrite from contacting with water and carbon dioxide and stabilize the surface structure of the material. At the same time, due to the high porosity, good conductivity, and three-dimensional network structure of the MOFs-derived carbonized material, it can effectively increase the wettability of the electrolyte and reduce resistance, thereby improving the electronic and ionic conductivity of the lithium replenishment material, and making the material have more outstanding rate performance and cycle stability; that is, the synergistic combination of titanium doping and the carbonized carbon coating layer derived from the MOFs material improves the stability of the positive electrode lithium replenishment material, and the lithium replenishment effect is excellent, thereby achieving a simultaneous improvement in the battery's charge and discharge capacity, rate performance, and cycle stability.

[0009] In the present invention, titanium doping and the carbon coating layer derived from carbonization of MOFs materials are synergistic and indispensable. If the carbon coating layer is not obtained by carbonization of MOFs materials, but by carbonization of conventional carbon sources (such as glucose), the synergistic effect of titanium doping cannot be exerted.

[0010] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0011] Preferably, the metal elements in the MOFs material include iron and / or zinc.

[0012] In a second aspect, the present invention provides a method for preparing the positive electrode lithium supplement material as described in the first aspect, the preparation method comprising the following steps:

[0013] Mixing a lithium source, an iron source and a titanium source at one time, and sintering to obtain a titanium-doped lithium ferrite material;

[0014] The titanium-doped lithium titanate material and the MOFs material are mixed for a second time and carbonized to obtain the positive electrode lithium supplement material.

[0015] The preparation method provided by the present invention realizes in-situ doping of titanium into the lithium ferrite material, and further obtains a positive electrode lithium replenishing material with good stability and excellent lithium replenishing effect through coating and carbonization of the MOFs material. The preparation method is simple to operate and is suitable for large-scale production.

[0016] Preferably, the molar ratio of lithium in the lithium source, iron in the iron source and titanium in the titanium source is (5-6):1:(0.01-0.05), for example 5:1:0.01, 5:1:0.02, 5:1:0.03, 5:1:0.04, 5.2:1:0.015, 5:1:0.05, 5.5:1:0.01, 5.5:1:0.02, 5.5:1:0.03, 5.5:1:0.04 or 5.5:1:0.05, 5.8:1:0.03, 6:1:0.01, 6:1:0.02, 6:1:0.03, 6:1:0.04 or 6:1:0.05, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] In the present invention, by adjusting the molar ratio of lithium in the lithium source, iron in the iron source and titanium in the titanium source to (5-6):1:(0.01-0.05), the doping of titanium element can be better achieved, the process is easy to manufacture, and the lithium supplementation effect is good.

[0018] It should be noted that the specific types of lithium source, iron source and titanium source in the present invention are all selected according to conventional technology, and the present invention is applicable to any type of material that can be used to prepare titanium-doped lithium ferrite that is reasonably known to those skilled in the art.

[0019] Optionally, the lithium source includes but is not limited to at least one of lithium carbonate, lithium oxide, lithium hydroxide monohydrate, lithium hydroxide, lithium bicarbonate or lithium nitrate; the iron source includes but is not limited to at least one of iron oxide, ferrous sulfate heptahydrate, ferric phosphate or ferric chloride; the titanium source includes but is not limited to at least one of titanium dioxide, titanium oxide or tetrabutyl titanate.

[0020] Preferably, the one-step mixing method comprises liquid phase mixing.

[0021] Preferably, the primary mixing includes sequentially performing low-speed mixing and high-speed mixing.

[0022] In the present invention, low-speed mixing and high-speed mixing refer to the relative high and low rotation speeds, and the relatively higher rotation speed is the low-speed mixing process, while the relatively higher rotation speed is the high-speed mixing process.

[0023] In the process of mixing the lithium source, the iron source and the titanium source, the invention uses a mixing method of first low speed and then high speed, which is more conducive to the mixing of various elements and the doping of the titanium source.

[0024] Preferably, the rotation speed of the low-speed mixing is 800-1000 r / min, for example, 800 r / min, 825 r / min, 850 r / min, 875 r / min, 900 r / min, 925 r / min, 950 r / min, 975 r / min or 1000 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Preferably, the low-speed mixing time is 1 to 3 hours, such as 1 hour, 2 hours or 3 hours, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0026] Preferably, the rotation speed of the high-speed mixing is 2000-3000 r / min, for example 2000 r / min, 2100 r / min, 2200 r / min, 2300 r / min, 2400 r / min, 2500 r / min, 2600 r / min, 2700 r / min, 2800 r / min, 2900 r / min or 3000 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] The invention further adjusts the low-speed mixing speed to 800-1000 r / min and / or the high-speed mixing speed to 2000-3000 r / min, so that the materials are mixed more evenly and the distribution of titanium is also more even.

[0028] Preferably, the high-speed mixing time is 2 to 5 hours, such as 2 hours, 3 hours, 4 hours or 5 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] Preferably, the once mixed material is spray dried and then sintered.

[0030] In the present invention, the once mixed material is subjected to spray drying treatment, so that the obtained dry product has uniform particle size distribution, regular shape, and compact and stable structure.

[0031] It should be noted that the specific preparation parameters of the spray drying in the present invention can be adaptively selected and adjusted by those skilled in the art according to actual needs.

[0032] Optionally, during the spray drying process, the outlet temperature can be adjusted to 180-200°C, for example, 180°C, 190°C or 200°C, and the feed rate is about 10-30mL / min, for example, 10mL / min, 15mL / min, 20mL / min, 25mL / min or 30mL / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] Preferably, the sintering temperature is 700-900°C, for example, 700°C, 750°C, 800°C, 850°C or 900°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] Preferably, the sintering time is 10 to 20 hours, for example 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours or 20 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In the present invention, the sintering atmosphere is a protective atmosphere, including a nitrogen atmosphere or an inert gas atmosphere.

[0036] Preferably, the mass ratio of the MOFs material to the titanium-doped lithium ferrite material is (1-3):(5-8), for example 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1.5:5.5, 1:8, 2:5, 2:5.5, 2:6, 2:6.5, 2:7, 2:7.5, 2:8, 2.5:7, 3:5, 3:5.5, 3:6, 3:6.5, 3:7, 3:7.5 or 3:8, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] The present invention also better controls the amount of the coating material by adjusting the mass ratio of the MOFs material to the titanium-doped lithium ferrite material to (1-3): (5-8), thereby achieving a better coating effect.

[0038] Preferably, the rotation speed of the secondary mixing is 800-1800r / min, for example 800r / min, 900r / min, 1000r / min, 1100r / min, 1200r / min, 1300r / min, 1400r / min, 1500r / min, 1600r / min, 1700r / min or 1800r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] Preferably, the secondary mixing time is 0.5 to 2.5 h, such as 0.5 h, 1 h, 1.5 h, 2 h or 2.5 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0040] Preferably, the carbonization includes performing a first carbonization and a second carbonization in sequence.

[0041] Preferably, the first carbonization includes a first temperature increase and a first temperature decrease.

[0042] Preferably, the first heating rate is 2 to 10°C / min, for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] Preferably, the temperature after the first heating is 450-550°C, for example 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C or 550°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] Preferably, the insulation time after the first heating is 6.5 to 7.5 hours, such as 6.5 hours, 7 hours or 7.5 hours, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] Preferably, the first cooling includes naturally cooling the temperature after the first heating to room temperature.

[0046] Preferably, the second carbonization includes a second temperature increase and a second temperature decrease.

[0047] Preferably, the second heating rate is 2-5°C / min, such as 2°C / min, 3°C / min, 4°C / min or 5°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] Preferably, the temperature after the second heating is 650-900°C, for example 650°C, 700°C, 750°C, 800°C, 850°C or 900°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] Preferably, the insulation time after the second heating is 8 to 11 hours, such as 8 hours, 9 hours, 10 hours or 11 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] Preferably, the second cooling includes naturally cooling the temperature after the second heating to room temperature.

[0051] It should be noted that the room temperature in the present invention is about 20-30° C., and can be adaptively selected and adjusted according to the specific reaction environment.

[0052] In the carbonization process of the present invention, the carbonization atmosphere is a conventional protective atmosphere, such as a nitrogen atmosphere or an inert gas atmosphere (such as argon or helium).

[0053] It should also be noted that the MOFs material in the present invention can be purchased directly or prepared by conventional preparation methods.

[0054] Exemplarily, the present invention provides a method for preparing a MOFs material, the preparation method comprising:

[0055] The metal salt, the organic ligand and the solvent are mixed, stirred evenly and then heated to react to obtain a metal organic framework material (MOFs material).

[0056] Optionally, the metal salt is selected from zinc salts and / or iron salts; the zinc salt is selected from zinc nitrate hexahydrate and / or zinc chloride; the iron salt is selected from at least one of ferric chloride, ferric nitrate or ferric sulfate.

[0057] Optionally, the organic ligand is selected from at least one of trimesic acid, 2-methylimidazole, thiophene-2,5-dicarboxylic acid or 2,5-dihydroxyterephthalic acid.

[0058] Optionally, the solvent is an organic solvent selected from at least one of methanol, acetone, ether or N,N-dimethylformamide.

[0059] Optionally, the reaction temperature of the heating reaction is 150-180°C, for example, 150°C, 160°C, 170°C or 180°C, and the reaction time of the heating reaction is 15-48h, for example, 15h, 18h, 20h, 24h, 25h, 27h, 30h, 35h, 36h, 38h, 40h, 42h, 45h or 48h, etc.

[0060] The molar ratio of the metal salt to the organic ligand is 5:(1-3), such as 5:1, 5:1.5, 5:2, 5:2.5 or 5:3, etc. The solvent is used to completely dissolve the reactants.

[0061] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the positive electrode lithium replenishing material as described in the first aspect and / or the positive electrode lithium replenishing material prepared by the preparation method as described in the second aspect.

[0062] In a fourth aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the third aspect.

[0063] Compared with the prior art, the present invention has the following beneficial effects:

[0064] In the present invention, titanium doping can increase the lattice defects of lithium ferrite materials, which is beneficial to improve Li + The diffusion rate inside the material and the conductivity of the particles effectively improve the initial charging capacity of the lithium-ion battery and improve the problem of capacity attenuation after the first charge; the synergistic combination of the carbonized carbon coating layer derived from the MOFs material, which is also doped with metal elements in the MOFs material, can prevent lithium ferrite from contacting with water and carbon dioxide and stabilize the surface structure of the material. At the same time, due to the high porosity, good conductivity, and three-dimensional network structure of the MOFs-derived carbonized material, it can effectively increase the wettability of the electrolyte and reduce resistance, thereby improving the electronic and ionic conductivity of the lithium replenishment material, and making the material have more outstanding rate performance and cycle stability; that is, the synergistic combination of titanium doping and the carbonized carbon coating layer derived from the MOFs material improves the stability of the positive electrode lithium replenishment material, and the lithium replenishment effect is excellent, thereby achieving a simultaneous improvement in the battery's charge and discharge capacity, rate performance, and cycle stability. DETAILED DESCRIPTION

[0065] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0066] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.

[0067] In the description of this application, the technical terms "primary", "secondary", "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0068] Example 1

[0069] This embodiment provides a positive electrode lithium replenishing material, which includes a core and a carbon coating layer coated on the surface of the core; the core includes titanium-doped lithium ferrite material, and the carbon in the carbon coating layer is derived from MOFs material and carbonized, and the MOFs material is a zinc-based MOFs material.

[0070] The preparation method of the positive electrode lithium supplement material is as follows:

[0071] S1:

[0072] Preparation of titanium-doped lithium ferrite material: weigh 5g of lithium carbonate, weigh ferric chloride and titanium dioxide according to the element atomic ratio of Li:Fe:Ti=5.2:1:0.015, dissolve in 50mL of deionized water to obtain a mixed solution, use a basket grinder to grind the mixed solution at a low speed of 850r / min for 2.5h (low-speed mixing), and then grind it at a high speed of 2300r / min for 4.5h (high-speed mixing) to obtain a mixed solution; use a spray drying instrument to spray dry the mixed solution, adjust the outlet temperature to 185°C, and the feed rate is 15mL / min, then place the spray-dried mixture in a muffle furnace under a protective atmosphere (nitrogen) and sinter at 750°C for 18h, and after cooling, crush, pulverize and sieve to obtain the titanium-doped lithium ferrite material;.

[0073] Preparation of MOFs material: Take 5g of zinc chloride, sample zinc chloride and 2-methylimidazole at a molar ratio of 5:1.2, dissolve in 50mL of methanol, mix and stir evenly, place in a reactor, and heat at 150°C for 45h to obtain zinc-based MOFs material;

[0074] S2:

[0075] The MOFs material and the titanium-doped lithium ferrite material are mixed and ball-milled. During the grinding process, the rotation speed is 900 rpm and the sand milling time is 2 hours. The mass ratio of the MOFs material to the titanium-doped lithium ferrite material is 1.5:5.5. The ball-milled material is placed in a tubular furnace, and the temperature is increased to 450°C at a rate of 3°C / min in high-purity nitrogen, and the temperature is kept for 7.3 hours. The material is naturally cooled to room temperature in an inert atmosphere furnace (the first carbonization stage), and then the temperature is increased to 700°C at a rate of 3°C / min, and the temperature is kept for 10 hours. The material is naturally cooled to room temperature in an inert atmosphere furnace again (the second carbonization stage) to obtain the positive electrode lithium supplement material.

[0076] Example 2

[0077] The present embodiment provides a positive electrode lithium replenishing material, which includes a core and a carbon coating layer coated on the surface of the core; the core includes titanium-doped lithium ferrite material, and the carbon in the carbon coating layer is derived from MOFs material and carbonized, and the MOFs material is an iron-based MOFs material.

[0078] The preparation method of the positive electrode lithium supplement material is as follows:

[0079] S1:

[0080] Preparation of titanium-doped lithium ferrite material: weigh 5g of lithium carbonate, weigh iron phosphate and titanium dioxide according to the element atomic ratio of lithium carbonate, ferric chloride and titanium dioxide of Li:Fe:Ti=5.5:1:0.02, dissolve in 50mL of deionized water to obtain a mixed solution, use a basket grinder to grind the mixed solution at a low speed of 900r / min for 2h, and then grind it at a high speed of 2600r / min for 4h to obtain a mixed solution; use a spray drying instrument to spray dry the mixed solution, adjust the outlet temperature to 190°C, and the feed rate is 20mL / min, then place the spray-dried mixture in a muffle furnace under a protective atmosphere (nitrogen) and sinter at 800°C for 15h, and after cooling, crush, pulverize and sieve to obtain the titanium-doped lithium ferrite material;.

[0081] Preparation of MOFs materials: Take 5 g of ferric sulfate, sample ferric sulfate and 2-methylimidazole at a molar ratio of 5:1.5, dissolve in 50 mL of methanol, mix and stir evenly, place in a reactor, and heat at 160 ° C for 35 h to obtain an iron-based MOFs material;

[0082] S2:

[0083] The MOFs material and the titanium-doped lithium ferrite material are mixed and ball-milled. During the grinding process, the rotation speed is 1200 rpm and the sand milling time is 1.5 hours. The mass ratio of the MOFs material to the titanium-doped lithium ferrite material is 2:6. The ball-milled material is placed in a tubular furnace, and the temperature is increased to 500°C at a rate of 5°C / min in high-purity nitrogen, and kept warm for 7 hours. It is naturally cooled to room temperature in an inert atmosphere furnace, and then the temperature is increased to 800°C at a rate of 4°C / min, and kept warm for 9 hours. It is naturally cooled to room temperature in the furnace in an inert atmosphere again to obtain the positive electrode lithium supplement material.

[0084] Example 3

[0085] This embodiment provides a positive electrode lithium replenishing material, which includes a core and a carbon coating layer coated on the surface of the core; the core includes titanium-doped lithium ferrite material, and the carbon in the carbon coating layer is derived from MOFs material and carbonized, and the MOFs material is a zinc-based MOFs material.

[0086] The preparation method of the positive electrode lithium supplement material is as follows:

[0087] S1:

[0088] Preparation of titanium-doped lithium ferrite material: weigh 5g of lithium carbonate, weigh ferric chloride and titanium dioxide according to the element atomic ratio of Li:Fe:Ti=5.8:1:0.03, dissolve in 50mL of deionized water to obtain a mixed solution, use a basket grinder to grind the mixed solution at a low speed of 950r / min for 1.5h, and then grind it at a high speed of 2800r / min for 3h to obtain a mixed solution; use a spray drying instrument to spray dry the mixed solution, adjust the outlet temperature to 190°C, and the feed rate is 20mL / min, then place the spray-dried mixture in a muffle furnace under a protective atmosphere (nitrogen) and sinter at 850°C for 13h, and after cooling, crush, pulverize and sieve to obtain the titanium-doped lithium ferrite material;.

[0089] Preparation of MOFs material: Take 5g of zinc chloride, sample zinc chloride and 2-methylimidazole in a molar ratio of 5:2, dissolve in 50mL of methanol, mix and stir evenly, place in a reactor, and heat at 170°C for 25h to obtain zinc-based MOFs material;

[0090] S2:

[0091] The MOFs material and the titanium-doped lithium ferrite material are mixed and ball-milled. During the grinding process, the rotation speed is 1500 rpm and the sand milling time is 1 hour. The mass ratio of the MOFs material to the titanium-doped lithium ferrite material is 2.5:7. The ball-milled material is placed in a tubular furnace, and the temperature is increased to 550°C at a rate of 6°C / min in high-purity nitrogen, and the temperature is kept for 6.5 hours. The material is naturally cooled to room temperature in an inert atmosphere furnace (the first carbonization stage), and then the temperature is increased to 850°C at a rate of 5°C / min, and the temperature is kept for 8 hours. The material is naturally cooled to room temperature in an inert atmosphere furnace again (the second carbonization stage) to obtain the positive electrode lithium supplement material.

[0092] Example 4

[0093] The difference between this embodiment and embodiment 1 is that in step S1 of this embodiment, lithium carbonate, ferric chloride and titanium dioxide are weighed in an atomic ratio of Li:Fe:Ti=5.2:1:0.05.

[0094] The rest of the preparation methods and parameters were the same as those in Example 1.

[0095] Example 5

[0096] The difference between this embodiment and embodiment 1 is that in step S2 of this embodiment, the mass ratio of MOFs material to titanium-doped lithium ferrite material is 1:8.

[0097] The rest of the preparation methods and parameters were the same as those in Example 1.

[0098] Example 6

[0099] The difference between this embodiment and embodiment 1 is that in step S2 of this embodiment, the mass ratio of MOFs material to titanium-doped lithium ferrite material is 3:5.

[0100] The rest of the preparation methods and parameters were the same as those in Example 1.

[0101] Example 7

[0102] The difference between this embodiment and embodiment 1 is that in step S1 of this embodiment, lithium carbonate, ferric chloride and titanium dioxide are weighed in an element atomic ratio of Li:Fe:Ti=5.2:1:0.005.

[0103] The rest of the preparation methods and parameters were the same as those in Example 1.

[0104] Example 8

[0105] The difference between this embodiment and embodiment 1 is that in this embodiment, in step S1, lithium carbonate, ferric chloride and titanium dioxide are weighed in an atomic ratio of Li:Fe:Ti=5.2:1:0.08.

[0106] The rest of the preparation methods and parameters were the same as those in Example 1.

[0107] Example 9

[0108] The difference between this embodiment and the embodiment is that in step S2 of this embodiment, the mass ratio of MOFs material to titanium-doped lithium ferrite material is 4:5.

[0109] The rest of the preparation methods and parameters were the same as those in Example 1.

[0110] Example 10

[0111] The difference between this embodiment and the embodiment is that in step S2 of this embodiment, the mass ratio of MOFs material to titanium-doped lithium ferrite material is 1:10.

[0112] The rest of the preparation methods and parameters were the same as those in Example 1.

[0113] Comparative Example 1

[0114] The difference between this comparative example and Example 1 is that the positive electrode lithium supplement material in this comparative example is pure lithium ferrite positive electrode material;

[0115] In the preparation method, tetrabutyl titanate is not added in step S1, and the preparation of MOFs material and step S2 are not performed.

[0116] The rest of the preparation methods and parameters were the same as those in Example 1.

[0117] Comparative Example 2

[0118] The difference between this comparative example and Example 1 is that in the positive electrode lithium supplement material of this comparative example, the lithium ferrite in the core is not doped with titanium;

[0119] In the preparation method, tetrabutyl titanate is not added in step S1.

[0120] The rest of the preparation methods and parameters were the same as those in Example 1.

[0121] Comparative Example 3

[0122] The difference between this comparative example and Example 1 is that the positive electrode lithium supplement material of this comparative example does not contain a coating layer;

[0123] In the preparation method, the preparation process of the MOFs material in step S1 and step S2 are not performed.

[0124] The rest of the preparation methods and parameters were the same as those in Example 1.

[0125] Comparative Example 4

[0126] The difference between this comparative example and Example 1 is that the carbon coating layer in this comparative example is obtained by carbonizing glucose;

[0127] In the preparation method, the preparation process of the MOFs material in step S1 is not performed, and the carbon source in step S2 is glucose.

[0128] The rest of the preparation methods and parameters were the same as those in Example 1.

[0129] [Button cell preparation and testing]

[0130] The positive electrode lithium supplement materials provided in Examples 1-10 and Comparative Examples 1-4 were directly used as positive electrode materials to prepare button-type batteries. The specific preparation process is as follows:

[0131] The positive electrode lithium supplement material, CNT, conductive carbon black and polyvinylidene fluoride binder provided in the embodiment and the comparative example are mixed in a mass ratio of 96.8:0.5:0.7:2, and NMP solvent is added. The mixture is stirred under the action of a vacuum stirrer until the system is uniform to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on one side of the positive electrode current collector aluminum foil, and dried. After drying, the mixture is rolled to obtain a positive electrode sheet.

[0132] Preparation of negative electrode sheet: Lithium sheet is selected as negative electrode sheet.

[0133] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0134] Preparation of diaphragm: Polypropylene film is selected as the diaphragm.

[0135] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a CR2032 button battery is obtained.

[0136] The button cell was subjected to a performance test under the following conditions:

[0137] At 25℃, charge to 4.1V at 0.1C constant current and constant voltage, cut off current 0.05C, leave for 30min, discharge to 2.5V at 0.1C constant current, and get the first week capacity. The test results are shown in Table 1.

[0138] Table 1

[0139] Button cell battery first week capacity (mAh / g) Example 1 736 Example 2 737 Example 3 742 Example 4 738 Example 5 735 Example 6 737 Example 7 729 Example 8 733 Example 9 731 Example 10 727 Comparative Example 1 706 Comparative Example 2 721 Comparative Example 3 719 Comparative Example 4 723

[0140] [Soft pack battery preparation and testing]

[0141] The positive electrode sheet preparation process provided in Examples 1-10 and Comparative Examples 1-4 was used as a lithium supplement material to prepare a soft-pack battery. The specific preparation process is as follows:

[0142] Preparation of the positive electrode sheet: lithium iron phosphate, the positive electrode lithium supplement material provided in Example 1, CNT, conductive carbon black and polyvinylidene fluoride binder are mixed in a mass ratio of 94.8:2:0.5:0.7:2, NMP solvent is added, and the mixture is stirred under the action of a vacuum stirrer until the system is uniform to obtain a positive electrode slurry, and the positive electrode slurry is evenly coated on the surface of one side of the positive electrode current collector aluminum foil, and dried, and then rolled to obtain a positive electrode sheet.

[0143] Preparation of negative electrode sheet: Graphite, conductive carbon black, CMC thickener and SBR binder are mixed in a mass ratio of 95.5:1:1.5:2, deionized water is added to mix to obtain negative electrode slurry, and then the negative electrode material is coated on one side of the copper foil, dried, and rolled to obtain the negative electrode sheet.

[0144] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0145] Preparation of diaphragm: Polypropylene film is selected as the diaphragm.

[0146] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a soft-pack battery is assembled.

[0147] The soft pack battery is subjected to performance test under the following test conditions:

[0148] a) First cycle capacity test: 25℃, charge to 4.1V at 0.1C constant current and constant voltage, cut off current 0.05C, leave for 30min, discharge to 2.5V at 0.1C constant current.

[0149] b) 300-cycle test: Cycle test: 25°C, charge to 3.65V at 1C constant current and constant voltage, cut off current 0.05C, leave for 30 minutes, discharge to 2.5V at 1C constant current, repeat 300 cycles.

[0150] c) Rate performance test:

[0151] At 25℃, charge to 3.65V at 0.5C constant current and constant voltage, cut off current at 0.05C, leave for 10min, discharge to 2.5V at 0.5C constant current, leave for 10min.

[0152] Charge to 3.65V at 0.5C constant current and constant voltage, cut off current at 0.05C, leave for 10 minutes, discharge to 2.5V at 1C constant current, leave for 10 minutes.

[0153] Charge to 3.65V at 0.5C constant current and constant voltage, cut off current at 0.05C, leave for 10 minutes, discharge to 2.5V at 2C constant current, leave for 10 minutes.

[0154] Charge to 3.65V at 0.5C constant current and constant voltage, cut off current at 0.05C, leave for 10 minutes, discharge to 2.5V at 3C constant current, leave for 10 minutes.

[0155] The test results of the above tests are shown in Table 2.

[0156] Table 2

[0157]

[0158]

[0159] In summary, in the present invention, titanium doping can increase the lattice defects of lithium ferrite materials, which is beneficial to improve Li + The diffusion rate inside the material and the conductivity of the particles effectively improve the initial charging capacity of the lithium-ion battery and improve the problem of capacity attenuation after the first charge; the synergistic combination of the carbonized carbon coating layer derived from the MOFs material, which is also doped with metal elements in the MOFs material, can prevent lithium ferrite from contacting with water and carbon dioxide and stabilize the surface structure of the material. At the same time, due to the high porosity, good conductivity, and three-dimensional network structure of the MOFs-derived carbonized material, it can effectively increase the wettability of the electrolyte and reduce resistance, thereby improving the electronic and ionic conductivity of the lithium replenishment material, and making the material have more outstanding rate performance and cycle stability; that is, the synergistic combination of titanium doping and the carbonized carbon coating layer derived from the MOFs material improves the stability of the positive electrode lithium replenishment material, and the lithium replenishment effect is excellent, thereby achieving a simultaneous improvement in the battery's charge and discharge capacity, rate performance, and cycle stability.

[0160] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A positive electrode lithium supplement material, characterized in that: The positive electrode lithium supplement material comprises a core and a carbon coating layer coated on the surface of the core; the core comprises titanium-doped lithium ferrite material, and the carbon in the carbon coating layer is derived from MOFs material and carbonized.

2. The positive electrode lithium supplement material according to claim 1, characterized in that: The metal elements in the MOFs material include iron and / or zinc.

3. A method for preparing a positive electrode lithium supplement material as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: Mixing a lithium source, an iron source and a titanium source at one time, and sintering to obtain a titanium-doped lithium ferrite material; The titanium-doped lithium titanate material and the MOFs material are mixed for a second time and carbonized to obtain the positive electrode lithium supplement material.

4. The preparation method according to claim 3, characterized in that: The molar ratio of lithium in the lithium source, iron in the iron source and titanium in the titanium source is (5-6):1:(0.01-0.05); Preferably, the one-step mixing method comprises liquid phase mixing; Preferably, the primary mixing includes sequentially performing low-speed mixing and high-speed mixing; Preferably, the rotation speed of the low-speed mixing is 800-1000 r / min, and the time of the low-speed mixing is 1-3 h; Preferably, the rotation speed of the high-speed mixing is 2000-3000 r / min, and the time of the high-speed mixing is 2-5 h.

5. The preparation method according to claim 3 or 4, characterized in that: The once mixed material is spray dried and then sintered; Preferably, the sintering temperature is 700-900° C., and the sintering time is 10-20 hours.

6. The preparation method according to claim 3, characterized in that: The mass ratio of the MOFs material to the titanium-doped lithium ferrite material is (1-3):(5-8); Preferably, the rotation speed of the secondary mixing is 800-1800 r / min, and the time of the secondary mixing is 0.5-2.5 h.

7. The preparation method according to claim 3 or 6, characterized in that: The carbonization includes sequentially performing a first carbonization and a second carbonization.

8. The preparation method according to claim 7, characterized in that: The first carbonization includes a first temperature increase and a first temperature decrease; Preferably, the heating rate of the first heating is 2 to 10°C / min, the temperature after the first heating is 450 to 550°C, and the holding time after the first heating is 6.5 to 7.5h; Preferably, the first cooling comprises naturally cooling the temperature after the first heating to room temperature; Preferably, the second carbonization includes a second temperature increase and a second temperature decrease; Preferably, the heating rate of the second heating is 2 to 5°C / min, the temperature after the second heating is 650 to 900°C, and the insulation time after the second heating is 8 to 11h; Preferably, the second cooling includes naturally cooling the temperature after the second heating to room temperature.

9. A positive electrode sheet, characterized in that: The positive electrode plate includes the positive electrode lithium replenishing material according to claim 1 or 2 and / or the positive electrode lithium replenishing material prepared by the preparation method according to any one of claims 3-8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 9.

Citation Information

Cited By

  • Battery monomer as well as preparation method and application thereof

    CN122068131A

  • Battery cells, their preparation methods and applications

    CN122068131B